Синтаксис любви: типология личности и прогноз парных отношений / А. Афанасьев - Афанасьев Александр Ю.
Экземпляры: аб. (2001) / Инвентарный номер: 43210 / Цена: / Сис.шифр: 88.37 / Авт.знак: А 94 / ГРНТИ: 15.21.51 / ББК: 88.37